Upaya Mengatasi Permasalahan Rendahnya Minat Belajar Siswa di Era Digital - Najah Tsabitah; Mamun Hanif (Jurnal Inovasi Pendidikan dan Ilmu Sosial, 2025)
The decline in students' learning interest in the digital era is influenced by several factors, including technological distractions, reduced face-to-face interaction, and lack of student motivation. Many students are more attracted to digital entertainment, as learning materials are perceived as less engaging. To address this issue, collaboration among educators, parents, and other relevant stakeholders is crucial in creating a supportive learning environment. Recommended strategies include the judicious use of technology, interactive learning, and active teaching methods that engage students. Providing positive feedback, personalized guidance, and project-based learning relevant to students' lives are also essential in enhancing their motivation. A conducive environment, such as family support, a comfortable school atmosphere, and positive social interactions, significantly influences students' interest in learning. The involvement of parents, creative educators, and a supportive learning environment will foster conditions that encourage greater student motivation and success in learning.